Economic policies and practices - Schnitzer, Martin; United States (Washington, U. S. Govt. Print. Off., 1964)
The major contribution of this study therefore lies not in developing new information, but in distilling the great variety of materials already available on European capital markets into a more relevant form for an American understanding of their functioning and development.
Materials prepared for the Joint Economic Committee Congress of the United States
osa 25/1/2019
Loans
Keywords: Unemployed; Sweden